Leptin levels in children with obstructive sleep apnea syndrome - (:unkn) unknown (TURKISH ASSOC TUBERCULOSIS & THORAX, 2016)
Introduction: The aim of this study is to assess the effect of obstructive sleep apnea syndrome (OSAS) severity on leptin levels in children. Patients and Methods: Children with habitual snoring underwent overnight polysomnography. Fasting venous blood samples were obtained between 8 AM and 9 AM, following the night of the sleep study. Children with an apnea-hypopnea index of >= 5/h were included in the moderate-to-severe OSAS group while those with an apnea-hypopnea index of < 5/h formed the mild OSAS/primary snoring group. Results: 47 children (51% male and 49% female; mean age 7.8 +/- 2.6 years) were recruited. Twenty seven participants were diagnosed with moderate-to-severe OSAS, and twenty children who had AHI < 5 were included in the mild OSAS/primary snoring. The two groups did not differ regarding age, gender and body mass index z score (p> 0.05). Furthermore there were no differences in log serum leptin levels (p= 0.749). Log serum leptin levels correlated with the BMI z score in the whole study group (p= 0.001; r= 0.499) but they were not associated with apnea-hypopnea index, mean and lowest oxygen saturation during sleep. Conclusion: Serum leptin levels are affected by adiposity but not by OSAS severity among children with habitual snoring.
Keywords: Leptin; obstructive sleep apnea syndrome; children; sleep apnea; C-REACTIVE PROTEIN; INSULIN-RESISTANCE; TURKISH CHILDREN; VASCULAR-DISEASE; OBESITY; ASSOCIATION; ADIPOKINES; SEVERITY; COHORT